Spatial distribution of fruit fly parasitoids (Diptera: Tephritidae) in comercial plantations in Brazil: a review (Research, Society and Development, 2022)
Fruit growing is an important sector of Brazilian agribusiness, which contributes to the economy, due to its potential for the production of various fruit trees. In this context, fruit flies have aroused concern, with the release of parasitoids in commercial orchards being common. The objective was to carry out a systematic bibliometric survey of fruit fly parasitoids in the main regions of Brazil, through articles published in journals from 2017 to 2021. The information presented was taken from the Capes Journal Portal, in the period of September 2021 to December 2021, using the keywords: “Fruit flies”, “Parasitoids” and “Biological control”. We found 21 articles in the databases, selecting 13 for this review. Based on the data of the articles found, related to the spatial distribution of parasitoids of fruit flies in commercial plantations in Brazil in the last five years, it demonstrates that the species T. anastrephae, D. areolatus, U. anastrephae parasitize the most of the fruit flies. fruits of the genus Anastrepha and Ceratitis.